PAUCIARTICULAR JUVENILE ARTHRITIS WITH ANF-ASSOCIATED UVEITIS: CLINICAL OBSERVATION OF A FAMILY CASE (MOTHER AND DAUGHTER) WITH ANKYLOSING SPONDYLITIS IN OUTCOME IN THE MOTHER - I. P. Nikishina; S. V. Arsenyeva; D. L. Alexeyev; A. V. Smirnov (Union of pediatricians of Russia, 2014)
Pauciarticular juvenile arthritis associated with antinuclear factor and uveitis with onset at an early age has a special place in the structure of juvenile arthrites. This variant of arthritis is characterized by unpredictability of nosological outcomes and the prognosis is often associated with unfavorable uveitis course. Joint syndrome is characterized by frequent dactylites, which are usually associated with psoriatic arthritis. The article presents clinical observation of a family case (mother and daughter) of juvenile arthritis with onset at an early age, eye lesion, homogenous clinical manifestations in the onset and manifestation of severe ankylosing spondylitis in the mother 25 years into the disease. Both patients started undergoing adalimumab therapy at the same time and very effectively. Clinical observation illustrates the need in timely prescription of a pathogenetically substantiated genetically engineered biological therapy in order to prevent incapacitation of patients with juvenile arthritis regarding condition of joints and organ of vision.